2008
DOI: 10.1111/j.1475-6811.2008.00208.x
|View full text |Cite
|
Sign up to set email alerts
|

The dominance dilemma: Do women really prefer dominant mates?

Abstract: Previous research has led to a widely accepted conclusion that heterosexual women prefer mates who are high in dominance. Three experiments designed to distinguish dominance from prestige and examine moderating contextual factors challenge this conclusion. College women at 2 U.S. universities evaluated hypothetical, potential mates described in written vignettes. Participants in Study 1 preferred a high‐prestige to a high‐dominance target. With dominance and prestige manipulated independently in Study 2, parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 59 publications
(79 reference statements)
5
48
0
1
Order By: Relevance
“…One hypothesis for why male chin shape is not more exaggerated is that some females may avoid mating with extremely aggressive males (Mueller and Mazur, 1998;Perrett et al, 1998;Swaddle and Reierson, 2002). In other words, some females may actually prefer mates with narrow chins, despite potentially lower genetic quality, since men that are perceived as less aggressive may also be perceived as better candidates for pair bonding (PentonVoak et al, 2004;Snyder et al, 2008). Studies have found that female facial preferences not only vary crossculturally , but also during a woman's menstrual cycle (Gangestand et al, 2004;Danel and Pawlowski, 2006).…”
Section: Discussionmentioning
confidence: 97%
“…One hypothesis for why male chin shape is not more exaggerated is that some females may avoid mating with extremely aggressive males (Mueller and Mazur, 1998;Perrett et al, 1998;Swaddle and Reierson, 2002). In other words, some females may actually prefer mates with narrow chins, despite potentially lower genetic quality, since men that are perceived as less aggressive may also be perceived as better candidates for pair bonding (PentonVoak et al, 2004;Snyder et al, 2008). Studies have found that female facial preferences not only vary crossculturally , but also during a woman's menstrual cycle (Gangestand et al, 2004;Danel and Pawlowski, 2006).…”
Section: Discussionmentioning
confidence: 97%
“…Dominant individuals were also found to signal their formidability by lowering their vocal pitch during the initial minutes of a group interaction, whereas those high in prestige do not systematically change their pitch (Cheng, Tracy, Ho, & Henrich, 2013). Individuals high in dominance versus prestige also demonstrate divergent hormonal (i.e., Testosterone) profiles (Johnson, Burk, & Kirkpatrick, 2007); patterns of economic decision making (Bruno, 2006;Halevy, Chou, Cohen, & Livingston, 2012); differential perceived attractiveness and desirability (Snyder, Kirkpatrick, & Barrett, 2008); and, in small-scale societies, reproductive success and nutritional health status (Reyes-Garcia et al, 2009;von Rueden, Gurven, & Kaplan, 2011). Collectively, these studies provide converging support for the claim that dominance and prestige are distinct and independent processes that simultaneously give rise to and underpin human rank relationships.…”
Section: The Dominance-prestige Account Of Social Rankmentioning
confidence: 99%
“…U.S. undergraduate women prefer prestigious men over dominant men as romantic partners, particularly in the context of long-term relationships [28].…”
Section: How Does Higher Social Status Lead To More Surviving Offspring?mentioning
confidence: 99%